Randomized, controlled pharmacokinetic and pharmacodynamic evaluation of albinterferon in patients with chronic hepatitis B infection - Colvin,R.A. (Wiley-Blackwell, 2015)
© 2014 Journal of Gastroenterology and Hepatology Foundation and Wiley Publishing Asia Pty Ltd. Background and Aims: Albinterferon is a fusion of albumin and interferon-α2b developed to improve the pharmacokinetics, convenience, and potential efficacy of interferon-α for the treatment of chronic hepatitis infections. Methods: This open-label, randomized, active-controlled, multicenter study investigated the safety and efficacy of albinterferon in patients with chronic hepatitis B virus (HBV) infection who were e-antigen (HBeAg) positive. One hundred and forty-one patients received one of four albinterferon doses/regimens or pegylated-interferon-α2a. Primary efficacy outcomes were changes in serum HBeAg and antibody, HBV-DNA, and alanine aminotransferase. Principal safety outcomes were changes in laboratory values, pulmonary function, and adverse events. Results: The study was prematurely terminated as phase III trials in hepatitis C infection indicated noninferior efficacy but inferior safety compared with pegylated-interferon-α2a. Here, all treatment groups had a significant reduction in HBV-DNA from baseline. Reductions in HBV-DNA were not significantly different, except the 1200μg every 4 weeks albinterferon dose which was inferior compared with pegylated-interferon-α2a. The serum alanine aminotransferase levels decreased in all arms. The per-patient incidence of adverse events was not significantly different for albinterferon (96.4-100%) and pegylated-interferon-α2a (93.1%). Total adverse events, however, were higher for albinterferon and correlated to dose. Decreased lung function was found in all arms (∼93% of patients), and was more common in some albinterferon groups. Conclusions: Albinterferon doses with similar anti-HBV efficacy to pegylated-interferon-α2a had higher rates of certain adverse events, particularly changes in lung diffusion capacity (http://www.clinicaltrials.gov number NCT00964665).